Upaya Perlindungan Hak-Hak Tersangka/Terdakwa Melalui Mekanisme Praperadilan di Kota Gorontalo - Dian Ekawaty Ismail; Yowan Tamu (Fakultas Hukum Universitas Gadjah Mada, 2009)
Building justice through judicature institution always contends with consequence which sacrifices the suspected as being object of investigation. There is a guarantee called “presumption of innocence”, but the guarantee is not representative enough, there must be still a guarantee that the position of the suspected is quiet strong, not only as object, but also, as possible as being subject, and law officers effort to find fair decisions. With the existing of prejudge, in hope, Criminal affairs will run well which is suitable with the current regulation. Arresting, jailing etc can not be accomplished at haphazard. The whole is to manifest law protection of human rights in order not to be violated. Besides it, the existence of prejudge in hope, is able to help and gives the protection of law to the basic rights of the accused as an effort to protect the one from forced trial by investigators and public prosecutors. Therefore, automatically the rights of the accused can also be protected. The execution of prejudge as managed within KUH Pidana is influenced by several factors such as: first, prejudge as the law protection of human rights. Second: prejudge as the instrument to control the investigator and prosecutor, Besides the factor as explained above, there are also barriers in the execution of prejudge. The hindering factor of prejudge execution consists, such as; First the prejudge practice is still rare. second, the basic difference of judge’s decision of sentence, third, limited time for inspection of prejudge affairs.